Réponses

2014-01-19T16:57:26+01:00
A) t(6t-18) = 0

t = 0

ou

6t-18 = 0
6t = 18
t = 3

Les solutions sont donc t=0 ou t=3

b) (x-2)(3x+5)


x - 2 = 0
x = 2

ou 

3x+5 = 0
3x = -5
 x = - \frac{5}{3}

les solutions sont donc t{0;3} et non t{1;3}
2014-01-19T16:59:53+01:00
A= 6t² - 18t 
A= 6t (6t - 3)

B= 3x(x-2)+5(x-2)
B= (x-2)(3x+5)

A= 6t² - 18t =0
6t (6t-3) = 0
6t = 0 OU 6t - 3 =0
6t/6 = 0/6 OU 6t = 3
t = 0 OU 6t/6 = 3/6
t = 0 OU t = 1/2

Les solutions sont t = 0 et t = 1/2.

B= 3x(x-2)+5(x-2)
(x-2)(3x+5)
x-2 = 0 OU 3x+5 = 0
x = 2 OU 3x = -5
x = 2 OU x = -5/3 

Les solutions sont x = 2 et x = -5/3.

Voilà
Discriminant : 36-4(1)(5) = 16
x1 : (6-4)/2 = 1
x2 : (6+4)/2 = 5
!!
ok